Book Reviews (The Muslim world, 1999)
Book reviewed in this article: Hezbollah: Born with a Vengeance The Succession to Muhammad: A Study of the Early Caliphate. Politics Without Process: Administering Development in the Arab World. Indian Muslims Since Independence. Militarism in Arab Society: An Historiographical and Bibliographical Sourcebook. I am a Palestinian Christian. The Agony of Algeria. The Middle East: From the End of Empire to the End of the Cold War. Liberal Islam: A Sourcebook. Hierarchy and Egalitarianiam in Islamic Thought. In Search of Islamic Feminism. One Woman's Global Journey. Daughters of Another Path. Experiences of American Women Choosing Islam.